Transcriptional Burst Initiation and Polymerase Pause Release Are Key Control Points of Transcriptional Regulation - Bartman, Caroline R.; Hamagami, Nicole; Keller, Cheryl A.; Giardine, Belinda; Hardison, Ross C.; Blobel, Gerd A.; Raj, Arjun (Molecular cell, 2019)
Transcriptional regulation occurs via changes to rates of different biochemical steps of transcription, but it remains unclear which rates are subject to change upon biological perturbation. Biochemical studies have suggested that stimuli predominantly affect the rates of RNA polymerase II (Pol II) recruitment and polymerase release from promoter-proximal pausing. Single-cell studies revealed that transcription occurs in discontinuous bursts, suggesting that features of such bursts like frequency and intensity could also be regulated. We combined Pol II chromatin immunoprecipitation sequencing (ChIP-seq) and single-cell transcriptional measurements to show that an independently regulated burst initiation step is required before polymerase recruitment can occur. Using a number of global and targeted transcriptional regulatory perturbations, we showed that biological perturbations regulated both burst initiation and polymerase pause release rates but seemed not to regulate polymerase recruitment rate. Our results suggest that transcriptional regulation primarily acts by changing the rates of burst initiation and polymerase pause release. [Display omitted] •Burst initiation is required before polymerase recruitment can occur•Biological stimuli changed only burst initiation and polymerase pause release rates•No biological stimuli tested altered polymerase recruitment rate Mammalian genes are transcribed in discontinuous bursts. Using experimental data and computational modeling, Bartman et al. show that the key control points of transcriptional regulation are burst initiation and the release of RNA polymerase II from a paused state, but, unexpectedly, not polymerase recruitment rate.